2015
DOI: 10.1080/13603124.2015.1023361
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of teachers for change in schools

Abstract: Theorizing on the role of teacher attitudes in change effectiveness, this study examined the predictive value of context (trust), process (social interaction, participative management and knowledge sharing) and outcome (job satisfaction and workload perception) variables for cognitive, emotional and intentional readiness of teachers for change. The study was designed as predictive correlational study. Data were collected from 1649 elementary teachers. Hierarchical linear regression analysis results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 65 publications
(76 reference statements)
1
34
0
1
Order By: Relevance
“…This kind of leadership has been shown to enhance the reform's impact on the educational reality (Alkahtani 2017;Boone 2014;Guhn 2009;Hargreaves and Fink 2006;Jones et al 2013;López-Yáñez and Sánchez-Moreno 2013;Toh 2016). Involving lots of stakeholders with different ideas of the intended change in the process (van den Akker 2003) as well as facilitating participation of those affected by the reforms requires leadership that promotes collective responsibility, mutual trust and inclusive membership as well as the creation of spaces in which to work together towards common goals (Adams 2013;Adams and Miskell 2016;Chow 2013;Horton and Martin 2013;Kondakci et al 2017;Stoll et al 2006). Such participatory leadership in change management creates opportunities for learning and reflective professional inquiry among the educational practitioners who ultimately implement the aims of the reform in the school (Leana 2011;López-Yáñez and Sánchez-Moreno 2013;Ramberg 2014;Thoonen et al 2012).…”
Section: The Top-down-bottom-up Implementation Strategymentioning
confidence: 99%
“…This kind of leadership has been shown to enhance the reform's impact on the educational reality (Alkahtani 2017;Boone 2014;Guhn 2009;Hargreaves and Fink 2006;Jones et al 2013;López-Yáñez and Sánchez-Moreno 2013;Toh 2016). Involving lots of stakeholders with different ideas of the intended change in the process (van den Akker 2003) as well as facilitating participation of those affected by the reforms requires leadership that promotes collective responsibility, mutual trust and inclusive membership as well as the creation of spaces in which to work together towards common goals (Adams 2013;Adams and Miskell 2016;Chow 2013;Horton and Martin 2013;Kondakci et al 2017;Stoll et al 2006). Such participatory leadership in change management creates opportunities for learning and reflective professional inquiry among the educational practitioners who ultimately implement the aims of the reform in the school (Leana 2011;López-Yáñez and Sánchez-Moreno 2013;Ramberg 2014;Thoonen et al 2012).…”
Section: The Top-down-bottom-up Implementation Strategymentioning
confidence: 99%
“…In a global environment where governments are setting ambitious goals for educational achievement, a key challenge in educational leadership is ensuring that teachers are well prepared in terms of their content knowledge, pedagogical practices, and attention to student growth (Stewart, ). There is wide acknowledgment that providing ongoing learning opportunities for teachers is a critical factor in sustaining a high‐quality teacher workforce and in implementing educational reforms (e.g., Cohen & Hill, ; Darling‐Hammond, ; Fullan, ), and that educational leaders play key roles in establishing the trust relationships and workforce environments that foster teachers' willingness and ability to implement changes in their practice (Kondakci, Beycioglu, Sincar, & Ugurlu, ; Liu & Hallinger, ). Over two decades of educational effectiveness research have demonstrated the link between teacher quality and student learning (e.g., Author et al, 2007; Darling‐Hammond, ; Muijs & Reynolds, ; Scheerens & Bosker, ), however, educational accountability policies often target improving student performance while failing to address instructional reform.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In this sense, policymakers and change leaders need to plan every phase in the change process, involve and inform all the stakeholders, and listen to their voices; and they must anticipate and plan for resistance to change (Shirley & Noble, 2016). More importantly, they must enhance teachers' readiness for change before initiating change as readiness for change is closely linked to the total experiences of teachers in their particular work settings (Kondakci, Beycioglu, Sincar, & Ugurlu, 2017). They need to conduct pilot studies, collect feedback about the process in the field of implementation, and make corrections if needed.…”
Section: Educational Implicationsmentioning
confidence: 99%